2021
DOI: 10.1186/s10194-021-01344-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence data on the monoclonal antibody erenumab in migraine prevention: perspectives of treating physicians in Germany

Abstract: Background Erenumab, the first-in-class fully human monoclonal antibody targeting the calcitonin gene-related peptide receptor, was shown to be efficacious and safe for the prophylactic treatment of migraine in adults in randomized clinical trials. Large-scale, real-world evidence in multi-centre settings is still needed to confirm these results. Erenumab patient profiles outside clinical trials and physicians’ treatment patterns, as well as data from patients treated in Germany, a severely imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 39 publications
4
3
0
Order By: Relevance
“…Our observations also accord with other studies of erenumab in the real world across a range of regions and settings [21][22][23][24][25]. For example, The TELESCOPE study, a multicentre survey collecting real-world data from 45 German headache centres, reported a 7.5 days reduction (p < 0.0001) in MHD following 3 months treatment with erenumab [25]. In another multicentre study in Italy (EARLY2), erenumab treatment reduced MHD by 12.8 ± 8.9 from baseline through week 45 to 48 [21].…”
Section: Discussionsupporting
confidence: 92%
“…Our observations also accord with other studies of erenumab in the real world across a range of regions and settings [21][22][23][24][25]. For example, The TELESCOPE study, a multicentre survey collecting real-world data from 45 German headache centres, reported a 7.5 days reduction (p < 0.0001) in MHD following 3 months treatment with erenumab [25]. In another multicentre study in Italy (EARLY2), erenumab treatment reduced MHD by 12.8 ± 8.9 from baseline through week 45 to 48 [21].…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this study represents the rst real-world evidence study of intravenous migraine treatment and the rst study examining the e cacy and tolerability of intravenous migraine medication among chronic and episodic migraine patients in the UAE. Similar to our study, other real-world data on other mAbs have validated our understanding of the effectiveness of these therapies [12,13]. Furthermore, the current study included diverse pools of patients in terms of their prior preventive therapies' exposure in their treatment; the inclusion of naïve patients, as well as those with PPTF for migraine headache allows for possible insights into how Eptinezumab-jjmr's e cacy may be impacted by prior medication history.…”
Section: Discussionsupporting
confidence: 66%
“…After the publication of the previous guideline, CGRP-mAbs became available in Europe and real-world observational studies confirmed the effectiveness of those drugs outside RCTs [ 31 34 ]. Tolerability and safety profiles were confirmed to be excellent and the adherence to treatment was not reported as a critical issue as it was with oral treatments [ 35 37 ].…”
Section: Resultsmentioning
confidence: 99%